2018 Fifth International Conference on Social Networks Analysis, Management and Security (SNAMS) 2018
DOI: 10.1109/snams.2018.8554956
|View full text |Cite
|
Sign up to set email alerts
|

A Multivalued Emotion Lexicon Created and Evaluated by the Crowd

Abstract: Sentiment analysis aims to uncover emotions conveyed through information. In its simplest form, it is performed on a polarity basis, where the goal is to classify information with positive or negative emotion. Recent research has explored more nuanced ways to perform emotion analysis. Unsupervised emotion analysis methods require a critical resource: a lexicon that is appropriate for the task at hand, in terms of the emotional range and diversity captured. Emotion analysis lexicons are created manually by doma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1

Relationship

5
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…All the models presented, and in extent their ensembles, can be further improved by a range of techniques. Test augmentation [70], hyperparameter optimization [71], bias reduction [72] and tailored emotional embeddings [4,73] are some techniques that could further improve the generalization capabilities of our networks. However, the computational load over multiple iterations is extensive, as the most complex models required hours of training per epoch and dataset.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All the models presented, and in extent their ensembles, can be further improved by a range of techniques. Test augmentation [70], hyperparameter optimization [71], bias reduction [72] and tailored emotional embeddings [4,73] are some techniques that could further improve the generalization capabilities of our networks. However, the computational load over multiple iterations is extensive, as the most complex models required hours of training per epoch and dataset.…”
Section: Resultsmentioning
confidence: 99%
“…Sentiment analysis is the process by which we uncover sentiment from information. The sentiment part could refer to polarity [1], fine grained or not [2], or to pure emotion information [3][4][5]. The most common source of information for sentiment analysis is Online Social Networks (OSNs) [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…During the analysis of the crowdsourcing results from one of our recent studies [9,12], we found evidence of high percentage of spam or dishonest contribution from workers originating from low income countries. Participants that deliver systematically the same contributions were identified as dishonest contributors, with high certainty.…”
Section: Introductionmentioning
confidence: 88%
“…In our study, each word is represented by the emotion it conveys. The Pure Emotion Lexicon (PEL) [11,7] contains a beyond polarity emotion vector, instead of a single emotion (MPQA, WordNet). The emotional vectors are normalised emotion classification results for each term and correspond to the eight basic emotions, as defined by Plutchik [18].…”
Section: Proposed Methodologymentioning
confidence: 99%